KUALITAS PELAYANAN BERBASIS DIGITAL DALAM PENGURUSAN NOMOR INDUK BERUSAHA (NIB) DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN KAMPAR - Ananda, Rizki Lestari; Andri, Seno; Meilani, Nur Laila (Jurnal Progress Administrasi Publik, 2023)
Kampar Regency is one of the districts in the Riau province which is also obliged to improve the quality of services to its people. One of the agencies that is heavily involved in providing services to the community directly and is the main door for almost all services managed by the community is the One Stop Integrated Investment and Licensing Service (DPMPTSP) of Kampar district. One type of service that is interesting to study is a service that uses the Online Single Submission (OSS) system. This service is a type of service that operates in the business licensing sector for both individuals and business entities. At the Kampar Regency DPMPTSP service, the OSS service offered is OSS-RBA or Online Single Submission -Riks Based Approach. Where is the service for business actors who want to take care of business permits such as business registration numbers or NIB. The research objective in this study is to determine the quality of digital-based services in managing business registration numbers at the Investment and One-Stop Integrated Services Department in Kampar Regency as well as the factors that are obstacles in determining the quality of digital-based services in managing business registration numbers at the investment office. Capital and One Stop Integrated Services in Kampar Regency. Sinambela Service Quality Theory in (Oscar., 2022). The method used is a qualitative type and an explanatory approach. The results obtained from this study are that the OSS RBA (Online Single Submission Risk Based Approach) service at the Kampar Regency Investment and One Stop Integrated Services Service is quite good and can be said to be of high quality   Keywords: Service Quality; NIB; OSS RBA.